Inpatients Perception about the Health Care Quality: Comparison of Public and Private Sector Hospitals in Karachi - M. Mumtaz Khan; Zaki Rashidi (JISR Management and Social Sciences & Economics, 2011)
This study was undertaken to analyze inpatients' perception about the health care quality in the hospitals of Karachi. As it was a comparative study, the population was divided into three groups. The inpatients perception was measured on the following variables: Communication quality of the health care service provider, experience of the health care service providers, quality of ward room and health care facility and the demeanor of the staff. The population was divided into three groups namely; public hospitals, private high hospitals, and private others. Sample size of hundred was drawn with convenience sampling from each of the three groups. Data was collected through a questionnaire developed on QSP (Quality Service Performance). The data analysis was done at two levels. The overall analysis of population was done for the sample size of 300. The analysis did not prove to be quiet revealing as the group effect caused the low performer to remain hidden behind the curtain of averages. The group comparison through one-way ANOVA proved to be the real opening. To support the findings of oneway ANOVA, relevant percentages were also calculated. Public sector hospitals and private others are found to be the group which needed improvement.